A surrogate cell‐based SARS‐CoV‐2 spike blocking assay. Issue 11 (28th September 2021) - Schuh, Wolfgang; Baus, Lena; Steinmetz, Tobit; Schulz, Sebastian R.; Weckwerth, Leonie; Roth, Edith; Hauke, Manuela; Krause, Sara; Morhart, Patrick; Rauh, Manfred; Hoffmann, Markus; Vesper, Niklas; et al.
Abstract: To monitor infection by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and successful vaccination against coronavirus disease 2019 (COVID‐19), the kinetics of neutralizing or blocking anti‐SARS‐CoV‐2 antibody titers need to be assessed. Here, we report the development of a quick and inexpensive su rrogate SARS‐CoV‐2 b locking a ssay (SUBA) using immobilized recombinant human angiotensin‐converting enzyme 2 (hACE2) and human cells expressing the native form of surface SARS‐CoV‐2 spike protein. Spike protein‐expressing cells bound to hACE2 in the absence or presence of blocking antibodies were quantified by measuring the optical density of cell‐associated crystal violet in a spectrophotometer. The advantages are that SUBA is a fast and inexpensive assay, which does not require biosafety level 2‐ or 3‐approved laboratories. Most importantly, SUBA detects blocking antibodies against the native trimeric cell‐bound SARS‐CoV‐2 spike protein and can be rapidly adjusted to quickly pre‐screen already approved therapeutic antibodies or sera from vaccinated individuals for their ACE2 blocking activities against any emerging SARS‐CoV‐2 variants. Abstract : A simple, inexpensive surrogate SARS‐CoV‐2 neutralization assay is introduced. Ectopic expression of the SARS‐CoV‐2 spike protein confers binding of Ramos‐Ig ‐ or HEK293 cells to plate‐bound recombinant human angiotensin‐converting‐enzyme‐2. This interaction can be blocked with reconvalescent or immune serum or with anti‐receptor‐binding domain antibodies. Bound spike‐expressing cells are quantitated with crystal violet.